An Evaluation of Evolutionary Constraints on Microsatellite Loci Using Null Alleles - Lehmann, T. (1996)
A test to evaluate constraints on the evolution of single microsatellite loci is described. The test assumes that microsatellite alleles that share the same flanking sequence constitute a series of alleles with a common descent that is distinct from alleles with a mutation in the flanking sequence. Thus two or more different series of alleles at a given locus represent the outcomes of different evolutionary processes. The higher rate of mutations within the repeat region (10(-3) or 10(-4)) compared with that of insertion/deletion or point mutations in adjacent flanking regions (10(-9)) or with that of recombination between the repeat and the point mutation (10(-6) for sequences 100 bp long) provides the rationale for this assumption. Using a two-phase, stepwise mutation model we simulated the evolution of a number of independent series of alleles and constructed the distributions of two similarity indices between pairs of these allele series. Applying this approach to empirical data from locus AG2H46 of Anopheles gambiae resulted in a significant excess of similarity between the main and the null series, indicating that constraints affect allele distribution in this locus. Practical considerations of the test are discussed.